Epithelial-to-Mesenchymal Transition in the Development and Progression of Adenocarcinoma and Squamous Cell Carcinoma of the Lung - Prudkin, Ludmila (2009)
Epithelial-to-mesenchymal transition is a process in which cells undergo a developmental switch from an epithelial to a mesenchymal phenotype. We investigated the role of this phenomenon in the pathogenesis and progression of adenocarcinoma and squamous cell carcinoma of the lung. Archived tissue from primary tumors (n=325) and brain metastases (n=48) and adjacent bronchial epithelial specimens (n=192) were analyzed for immunohistochemical expression by image analysis of E-cadherin, N-cadherin, integrin-αvβ6, vimentin, and matrix metalloproteinase-9. The findings were compared with patients’ clinicopathologic features. High expression of the epithelial-to-mesenchymal transition phenotype (low E-cadherin and high N-cadherin, integrin-αvβ6, vimentin, and matrix metalloproteinase-9) was found in most lung tumors examined, and the expression pattern varied according to the tumor histologic type. Low E-cadherin membrane and high N-cadherin cytoplasmic expression were significantly more common in squamous cell carcinoma than in adenocarcinoma (P=0.002 and 0.005, respectively). Dysplastic lesions had significantly lower expression of the epithelial-to-mesenchymal transition phenotype than did squamous cell carcinomas, and integrin-αvβ6 membrane expression increased stepwise according to the histopathologic severity. Brain metastases had decreased epithelial-to-mesenchymal transition expression compared with primary tumors. Brain metastases had significantly lower integrin-αvβ6 membrane (P=0.04) and N-cadherin membrane and cytoplasm (P<0.0002) expression than did primary tumors. The epithelial-to-mesenchymal transition phenotype is commonly expressed in primary squamous cell carcinoma and adenocarcinoma of the lung; this expression occurs early in the pathogenesis of squamous cell carcinoma. Brain metastases showed characteristics of reversed mesenchymal-to-epithelial transition. Our findings suggest that epithelial-to-mesenchymal transition is a potential target for lung cancer chemoprevention and therapy.